Revisiting Al-Faruqi’s Islamization of Knowledge: A Hermeneutic and Decolonial Analysis for Contemporary Epistemic Reform - Akhmad Jazuli Afandi; Muhyidin Muhyidin (International Journal of Religion and Social Community, 2025)
This study critically examines Ismail Raji Al-Faruqi's (1921-1986) Islamization of Knowledge (IOK) project, focusing on its philosophical consistency, real-world application, and connection to global decolonial ideas. Through a tripartite methodological approach combining critical hermeneutics, comparative epistemology, and empirical case studies, we assess the enduring contributions and limitations of Al-Faruqi's framework. Our textual analysis reveals that while the Tawhidic (Divine Unity) paradigm effectively challenges Western epistemological fragmentation, its potential for epistemic essentialism requires mitigation through greater contextual flexibility. Comparative examination demonstrates that IOK's five-step methodology, though theoretically robust for traditional disciplines, demands significant adaptation for contemporary challenges in STEM fields and digital humanities. Empirical investigations at institutions implementing IOK principles (including IIIT and IIUM) further identify a critical gap in addressing intra-Muslim power asymmetries, particularly regarding gender and cultural diversity in knowledge production. Building on these findings, the study proposes an enhanced "decolonial-Islamic" framework that: (1) maintains Al-Faruqi's core metaphysical foundations while incorporating pluralistic epistemological approaches; (2) develops discipline-specific adaptation protocols for emerging academic fields; and (3) integrates institutional assessment tools to evaluate Islamization outcomes. These contributions advance three key academic discourses: Islamic epistemology's engagement with decolonial theory, practical models for educational reform in Muslim-majority societies, and interdisciplinary approaches to knowledge decolonization. The paper concludes with policy recommendations for implementing this refined framework in contemporary Islamic higher education contexts.